Impact of Cigarette Smoking Status on Pain Intensity Among Veterans With and Without Hepatitis C. (7th September 2018) - Lynch, Shaina M; Wilson, Sarah M; DeRycke, Eric C; Driscoll, Mary A; Becker, William C; Goulet, Joseph L; Kerns, Robert D; Mattocks, Kristin M; Brandt, Cynthia A; Bathulapalli, Harini; Skanderson, Melissa; Haskell, Sally G; et al.
Abstract: Objective: Chronic pain is a significant problem in patients living with hepatitis C virus (HCV). Tobacco smoking is an independent risk factor for high pain intensity among veterans. This study aims to examine the independent associations with smoking and HCV on pain intensity, as well as the interaction of smoking and HCV on the association with pain intensity. Design/Particpants: Cross-sectional analysis of a cohort study of veterans of Operations Enduring Freedom/Iraqi Freedom/New Dawn (OEF/OIF/OND) who had at least one visit to a Veterans Health Administration (VHA) primary care clinic between 2001 and 2014. Methods: HCV was identified using ICD-9 codes from electronic medical records (EMRs). Pain intensity, reported on a 0–10 numeric rating scale, was categorized as none/mild (0–3) and moderate/severe (4–10). Results: Among 654, 841 OEF/OIF/OND veterans (median age [interquartile range] = 26 [23–36] years), 2, 942 (0.4%) were diagnosed with HCV. Overall, moderate/severe pain intensity was reported in 36% of veterans, and 37% were current smokers. The adjusted odds of reporting moderate/severe pain intensity were 1.23 times higher (95% confidence interval [CI] = 1.14–1.33) for those with HCV and 1.26 times higher (95% CI = 1.25–1.28) for current smokers. In the interaction model, there was a significant Smoking Status × HCV interaction ( P = 0.03). Among veterans with HCV, smoking had a significantly larger association with moderate/severe pain (adjusted odds ratio [OR] = 1.50, P < 0.001) than among veterans without HCV (adjusted OR = 1.26, P < 0.001). Conclusions: We found that current smoking is more strongly linked to pain intensity among veterans with HCV. Further investigations are needed to explore the impact of smoking status on pain and to promote smoking cessation and pain management in veterans with HCV.